Mechanical and tribological characterization of graphene nanoplatelets/Al2O3 reinforced epoxy hybrid composites - Kaykilarli, Cantekin; Yeprem, H. Ayguel; Uzunsoy, Deniz (TAYLOR & FRANCIS INC, 2023)
This study aimed to determine the effects of varying Aluminum oxide (Al2O3) and Graphene Nanoplatelets (GNP) concentrations on epoxy-based polymer composites' mechanical and tribological characteristics. Al2O3 (1 to 5 wt.%) and GNP (0 to 1 wt.%) reinforced epoxy matrix composites were produced with sonication and stirring magnetic route. Mechanical, microstructural and tribological properties of composites were investigated via X-ray diffraction (XRD), Archimedes' Method, Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Spectroscopy (EDX), Raman spectroscopy, hardness, impact, tensile, compressive and wear tests. The highest ultimate tensile strength and compressive strength were found at 62.83 and 137 MPa for 3 wt.% reinforced Al2O3 epoxy matrix composites, and it was observed that there was a 38% and 17% increase compared to neat epoxy, respectively. The highest impact strength was found for 3 wt.% Al2O3 and 1 wt.% GNP-reinforced composites and increased by 19% compared to neat epoxy. The best hardness was found for 3 wt.% reinforced Al2O3 and 0.25 wt.% GNP-reinforced composite, and there was a 22% increase in hardness compared to neat epoxy. Also, the highest wear resistance (1.686x10(-6) mm(3)/Nm) and lowest Coefficient of Friction (COF, 0.13755) were determined for the same specimen.
Keywords: Hybrid composites; epoxy; aluminum oxide; graphene; mechanical behavior; FRACTURE-TOUGHNESS; THERMAL-PROPERTIES; GRAPHITE; DISPERSION; MORPHOLOGY; NANOCOMPOSITES; PERFORMANCE; FRICTION; BEHAVIOR; TENSILE; Chemistry; Science & Technology - Other Topics; Materials Science; Physics